A summary of the body of knowledge on physical activity for people following stroke: a scoping review. (3rd September 2022) - McFeeters, Claire; Pedlow, Katy; Kennedy, Niamh; Colquhoun, Heather; McDonough, Suzanne
Abstract: Background: There are challenges implementing physical activity interventions for people across the stroke pathway of care. There is a need to understand the intervention content in addition to the effects. Objective: This scoping review maps out the existing systematic review evidence in relation to five objectives. Design: Intervention data were extracted to identify and clarify definitions of physical activity as well as key emerging themes, gaps and recommendations for implementation approaches and consensus. Results: 50 systematic reviews fulfilled the predefined inclusion criteria. Most reviews ( n = 31) focused on a subset of physical activity rather than day to day physical activity ( n = 19). In addition, a description of theories underpinning the interventions were lacking. Only 11 reviews used a definition of physical activity. Physical activity outcome measures were reported in 22 reviews. Conclusions: Better reporting of physical activity interventions is required to improve implementation. Research should include physical activity outcome measures across the stroke pathway. Determining which physical activity modes and parameters of each intervention would be useful in determining the optimal intervention for stroke survivors with different physical activity capacity levels.